Dampak Negatif Globalisasi pada Perilaku Generasi Milenial yang Bertentangan dengan Nilai-Nilai Pancasila - Advent Graceman Mendrofa; Amelia Nurlita; Ilham Hudi; Dimas Darma Putra; Dian Juniati Sandra Putri; Sakti Wibowo; Syarifatul Hayati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research investigates the negative impact of globalization on the behavior of the millennial generation which is contrary to the values ​​of Pancasila. Through qualitative methods and literature studies, this research collects and analyzes various relevant sources to understand how globalization has influenced the mindset and behavior of the millennial generation in the context of Pancasila values. This research aims to analyze the negative impact of globalization on the behavior of the millennial generation which is contrary to the values ​​of Pancasila. Qualitative methods and literature studies were used to explore various relevant sources, including academic journals, books and scientific articles. The research results show that globalization has had a significant impact on the behavior of the millennial generation, changing thought patterns and values ​​that may not be in line with Pancasila values. Factors such as the influence of social media, economic globalization, and pop culture can influence the attitudes and behavior of this generation. This research provides a deeper understanding of the dynamics between globalization and local values, especially Pancasila. The implications of these findings can be used as a basis for developing educational and social strategies to mitigate the negative impact of globalization on the millennial generation and strengthen awareness of the values ​​of Pancasila.